KEBIJAKAN PENDANAAN DAN DIVIDEN DENGAN PENDEKATAN ISVESTMENT OPPORTUNITY SET - Ulyah, Himmatul (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2018)
This study aims to see differences in funding policies and dividend policies between high-potential and high-growth manufacturing firms with Investment Opportunity Sets. The results show that there is a significant difference in funding policy between high-growth and potential firms with low-growth firms using investment opportunity sets. The resulting significant value is 0.014 where the value is lower than 0.05. There is a significant difference in the dividend policy between a highgrowth and high-potential manufacturing company with an investment opportunity set. The resulting significant value is 0.006 where the value is lower than 0.05.